2022
DOI: 10.3847/1538-4357/ac94ca
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of f(R) Gravity and Massive Neutrinos on the Turnaround Radii of Dark Matter Halos

Abstract: We present a new statistics based on the turnaround radii of cluster halos to break the dark sector degeneracy between the ΛCDM model and the alternative ones with f(R) gravity and massive neutrinos (ν) characterized by the strength of the fifth force, ∣f R0∣, and the total neutrino mass, M ν . Analyzing the Rockstar halo catalogs at the present epoch from the DUSTGRAIN-pathfinder N-body simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A hybrid of the two types of boundaries is the turnaround radius, which is a kinematically motivated boundary (the scale that separates a nonexpanding structure from the Hubble flow) that according to spherical collapse, also constitutes a scale of constant overdensity for collapsed structures of all masses at a given redshift. In recent years, the turnaround radius has gained considerable attention as a scale on which cosmological models can be tested (e.g., Pavlidou & Tomaras 2014; E-mail: gkorkidis@physics.uoc.gr Nojiri et al 2018;Capozziello et al 2019;Lopes et al 2019;Wong 2019;Pavlidou et al 2020;Santa Vélez & Enea Romano 2020;Del Popolo 2020;Faraoni et al 2020;Korkidis et al 2020;Lee & Baldi 2022). Pavlidou et al (2020) showed by employing the sphericalcollapse model that the matter density within the turnaround scale (the turnaround density, ρ ta ) could be used as a cosmologyprobing observable, with a number of attractive properties: For a given redshift, the turnaround density is universal and thus insensitive to halo size, selection biases, and sample completeness issues; its present-day value almost exclusively probes the matter density; and its evolution with redshift is sensitive to the dark energy content of the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid of the two types of boundaries is the turnaround radius, which is a kinematically motivated boundary (the scale that separates a nonexpanding structure from the Hubble flow) that according to spherical collapse, also constitutes a scale of constant overdensity for collapsed structures of all masses at a given redshift. In recent years, the turnaround radius has gained considerable attention as a scale on which cosmological models can be tested (e.g., Pavlidou & Tomaras 2014; E-mail: gkorkidis@physics.uoc.gr Nojiri et al 2018;Capozziello et al 2019;Lopes et al 2019;Wong 2019;Pavlidou et al 2020;Santa Vélez & Enea Romano 2020;Del Popolo 2020;Faraoni et al 2020;Korkidis et al 2020;Lee & Baldi 2022). Pavlidou et al (2020) showed by employing the sphericalcollapse model that the matter density within the turnaround scale (the turnaround density, ρ ta ) could be used as a cosmologyprobing observable, with a number of attractive properties: For a given redshift, the turnaround density is universal and thus insensitive to halo size, selection biases, and sample completeness issues; its present-day value almost exclusively probes the matter density; and its evolution with redshift is sensitive to the dark energy content of the Universe.…”
Section: Introductionmentioning
confidence: 99%